A day of pleasure stories of a boy growing up in Warsaw. - Singer, Isaac Bashevis 1904- (New York Farrar, 1969)
Nineteen autobiographical stories about the author's childhood in Poland from 1908 to 1918.
Autobiographical.
Keywords: Singer, Isaac Bashevis -- 1904-.; Singer, Isaac Bashevis -- 1904- -- Homes and haunts -- Poland -- Warsaw; Singer, Isaac Bashevis -- 1904- -- Childhood and youth; Authors, Yiddish -- Poland -- Warsaw -- Biography; Jews -- Poland -- Warsaw -- Biography; Warsaw (Poland) -- Social life and customs